2021
DOI: 10.1002/jssc.201901274
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and yield optimization of lipopeptides from Bacillus subtilis Z‐14 active against wheat take‐all caused by Gaeumannomyces graminis var. tritici

Abstract: Wheat take‐all, caused by the soil‐borne fungus Gaeumannomyces graminis var. tritici, is one of the major constraints on wheat production worldwide. Bacillus subtilis Z‐14 exerts significant biocontrol activity against wheat take‐all, and lipopeptide antibiotics are the main antifungal substances. Herein, lipopeptide antibiotics C14–C15 iturin A, C14–C16 fengycin A, and C15–C17 fengycin B from B. subtilis Z‐14 culture filtrates were separated and identified by high‐performance liquid chromatography, matrix‐ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It resulted in the significant control of the take-all disease in the disease caused by Gaeumannomyces graminis var. tritici and fruit gray mold caused by Botrytis cinerea. The fungus FOC was donated by Professor Jin Cheng of the Institute of Microbiology, Chinese Academy of Sciences . Uncoated cucumber seeds (Jinyan No.…”
Section: Methodsmentioning
confidence: 99%
“…It resulted in the significant control of the take-all disease in the disease caused by Gaeumannomyces graminis var. tritici and fruit gray mold caused by Botrytis cinerea. The fungus FOC was donated by Professor Jin Cheng of the Institute of Microbiology, Chinese Academy of Sciences . Uncoated cucumber seeds (Jinyan No.…”
Section: Methodsmentioning
confidence: 99%
“…Using lipopeptides directly to control plant diseases is not economical at present. However, as research on their synthetic regulatory mechanism and the yield optimization of lipopeptides progresses (Dang et al, 2019;Zhang et al, 2021), it will become increasingly realistic to use lipopeptides to control plant diseases to compensate for the deficiencies of using intact cells (Chakraborty et al, 2020;Kourmentza et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Methanol extracts of strain Z-14 fermentation supernatant were shown to contain three lipopeptide antibiotic families (surfactins, iturins, and fengycins). The combination of isolation using high performance liquid chromatography (HPLC), antifungal activity measurement via a diffusion plate assay, and component detection using MALDI-TOF MS analysis demonstrated that iturins and fengycins were the main antifungal metabolites of strain Z-14 (Zhang et al, 2021). The present study aimed to determine the differences in the antifungal mechanisms against the phytopathogenic fungus of iturins and fengycins purified from strain Z-14 fermentation supernatant, and their inhibitory spectrum against fungi and bacteria, using the wheat take-all pathogen and all the microorganisms in soil as indicators.…”
Section: Introductionmentioning
confidence: 99%
“…This class of lipopeptides was synthesized by modular nonribosomal peptide synthetases (NRPSs) ( 18 ). Previous studies in other Bacillus species suggested that NRP production correlated with expression of NRPS genes ( 19 20 ). Several regulatory genes of NRP biosynthesis were also determined ( 21 22 ).…”
Section: Introductionmentioning
confidence: 91%